„Wracają czasy Krzyża i Szabli”. Narodowo-radykalna krucjata przeciwko materializmowi. Myśl polityczna Mariana Reutta 1907–1945 w latach trzydziestych XX wieku - Meller, Arkadiusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The paper analyzes the intellectual achievements of Marian Reutt, one of the most important personalities of the Polish pre-war national radicalism. He was the first person to translate the works of the Russian historiosopher Nikolai Berdyaev into Polish. The author begins with the presentation of the basic facts from Reutt’s biography; in further parts the analysis of his political thought is conducted. The article focuses primarily upon demonstrating the historiosophic, political-and-legal and economic conceptions developed by Reutt. It should be remarked that, as far as social-and-political thought was concerned, Marian Reutt’s ideas were not much different from the proposals advocated by National Radical Movement “Phalanx” with which he was closely connected for the prevailing amount of time. What possibly made him different from other activists was his fascination with the Middle Ages which was probably caused by two factors. First, he considered this period in the development of Latin civilization to be the time of the primacy of spirit over matter. Second, according to Reutt’s somewhat doubtful view, it was a period of centralism and economic statism.
Keywords: Reutt, Marian (1907-1945); myśl polityczna II Rzeczypospolitej; Narodowy Ruch Radykalny „Falanga”